GENOME-WIDE IDENTIFICATION, CHARACTERIZATION, AND PHYLOGENETIC ANALYSIS OF CALCIUM-DEPENDENT PROTEIN KINASE IN ZEA MAYS - Srikanth Burra1, K. Venkata Naga Rajeshwari1, S. Suma*1 (Chelonian Research Foundation, 2023)
Plant growth and development, stress responses, senescence, and plant hormone signaling are just a few of the physiological processes for which calcium-dependent protein kinases (CDPKs) have been demonstrated to be crucial. We found 40 CDPK genes in our study by doing a bioinformatics analysis of the whole maize genome. Based on the phylogenetic study, 40 ZmCPKs are classified into four categories. we report a genome-wide analysis of the CDPK gene family in maize here. This genomic analysis of maize CDPK genes serves as a foundation for a functional investigation of this gene family in maize. Keywords: CDPK, Gene Family, Maize, phylogenetic analysis.